Sistem Monitoring Cairan Infus Terpusat Menggunakan Pengolahan Citra Digital - Ringga Aulia Primahayu; Fitri Utaminingrum; Dahnial Syauqy (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Imbalances between patient and medical personnel, especially nurses on duty 24 hours monitoring the condition of inpatients result in negligence. For example in terms of monitoring the condition of intravenous fluids. Based on these case examples, a system that is able to reduce the level of negligence and help the performance of medical personnel to improve hospital services. So to overcome this, a system designed to monitor intravenous fluids centrally using digital image processing. Some digital image processing methods used are thresholding to separate object image with the background, morphology to improve threshold image results by using dilation and erosion operation, moment invariant to describe characteristic shape and infusion fluid condition seen from a number of area and position. By using Raspberry Pi as a processing unit and sending information the infusion fluid condition is controlled centrally on the local network using TCP / IP socket as the communication medium to the server. The results of this study indicate that the system can detect infusion fluid conditions using several methods of processing digital images and send detection results to the server.